Skreening Alga Hijau Halimeda opuntia (Linnaeus) sebagai Antioksidan dari Pesisir Aceh Barat - Mohamad Gazali; . Nurjanah; Neviaty Putri Zamani (Jurnal Ilmu Pertanian Indonesia, 2019)
H. opuntia is one of the green algae that distributes sufficiently dominant at the coastal of West Aceh. This research aims to screen the green algae H. opuntia that is potentia as an antioxidant agent. Extraction method in this research used mono maceration. The solvents that are used including ethanol (polar), ethyl acetate (semi-polar), and n-hexane (non-polar). With those three solvents it was obtained three crude extracts including ethanol crude extract, ethyl acetate crude extract, and n-hexane crude extract. Subsequently, the crude extracts were used to conduct the assay including phytochemical assay and the antioxidant activity with DPPH method. The results of phytochemical assay showed that ethanol crude extract of H. opuntia was detected to have active compounds including alkaloids, flavonoid, phenol, tannin, and steroids whereas ethyl acetate extract of H. opuntia was detected to contain phenol compound. Total phenol content of ethanolic extract of H. opuntia = 2460.25 mg GAE/g and ethyl acetate extract = 972.68 mg GAE/g. Antioxidant activity of ethanolic extract has IC50 value = 143.63 mg/L whereas ethyl acetate extract has IC50 value = 75.51 mg/L with Vitamin C as a positive control. This results show that extract of H. opuntia possesses a vital potency as an antioxidant agent that give value added in pharmacy industries.